(untitled) (Homoeopathy for All, 2022)
Corona virus disease 2019 is an infectious disease caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2). This is firstly reported in December 2019 in Wuhan city of China and now this pandemic has become a global public health problem. Many people infected with COVID-19 virus may remain asymptomatic and some may experience mild to moderate respiratory illness. Many of them recover without any specific treatment, but older people and those with other medical problems like cardiovascular disease, chronic respiratory disease and diabetes are more prone to develop serious illness. Till now many therapies were developed for the treatment of covid 19 virus. Still vaccines and effective remedies are on development which are time consuming process because it needs pre clinical to clinical trials. So now it becomes essential to introduce the utility of alternative treatments such as of Ayurveda, Siddha, Homoeopathy or Unani. These ancient modes of treatments are very efficient and can save lives of sufferers in less time with less expenditure. Homoeopathy has benefitted human kind in epidemics since over the last centuries. In epidemic diseases, each case should be treated as a fresh one and studied thoroughly. After studying a number of patients, physician get to know about the true state of present illness and can select a suitable homoeopathic medicine called “Genus epidemicus”. This particular genus epidemicus can provide us with a safe and effective treatment in epidemic disease.